LANGUAGE OF THE ABSOLUTE: A CONTEMPORARY INDIAN INTERPRETATION - Basu, Arabinda (Journal of Dharma, 1992)
Sri Aurobindo has a distinctive theory of the origin, development, capacities and limitations of language and of Aryan speech. He planned a whole book on "The Origins of Aryan Speech"! It was unfortunate that other preoccupations prevented him from completing it, for to judge from the published portions of the proposed work, the complete treatise would have been most stimulating and thought provoking and given scholars in the field of linguistics very valuable guidelines for their research. It is not my purpose to expound the theory now. But a brief description of its main points will be in place because that has a bearing on our subject.